Clonal Characteristics of T-Cell Receptor Repertoires in Violent and Non-violent Patients With Schizophrenia - Li, Qiguang; Zhou, Jiansong; Cao, Xia; Liu, Qiang; Li, Qi; Li, Wen; Wang, Xiaoping (Frontiers in Psychiatry, 2018)
Background: Activated or impaired T-cell function in inflammatory and degenerative process can contribute to the risk and progression of schizophrenia. This study used immune repertoire sequencing to investigate the T-cell receptor beta variable chain (TRBV) presence in blood mononuclear cells in the violent or non-violent schizophrenic patients. Methods: 10 violent and 10 non-violent schizophrenic patients and 8 matched healthy controls were enrolled. The Brief Psychiatric Rating Scale (BPRS) was used to evaluate patients' psychiatric symptoms. The level of aggression was assessed using the Modified Overt Aggression Scale (MOAS). The complementarity-determining region 3 (CDR3) of TRBV was detected using multiplex-PCR and high-throughput sequencing. Results: The TCR repertoire diversity were no significant differences in the Shannon–Wiener or inverse Simpson diversity index between three groups. Principal component analysis (PCA) of TRBV composition and abundance showed that principal component 1 and principal component 2 can explain 28.88% and 13.24% of total variation, respectively. Schizophrenic patients (violent and non-violent) had significantly different V gene distribution compared to healthy controls. In particular, TRBV2 occurred at a significantly higher frequency in the violent schizophrenia group than in the non-violent schizophrenia and healthy control groups, and TRBV7-2 occurred at a significantly higher frequency in the non-violent schizophrenia group than in the violent schizophrenia and healthy control groups. Conclusions: The results suggest that violent and non-violent schizophrenic patients carry abnormal T-cell receptor repertoires, and these data provide a useful clue to explore the etiology of violent behavior in schizophrenia.